Konstruksi Diagram Potensial-pH untuk Baja Karbon dalam Buffer Asetat secara Potensiodinamik Eksperimental - Bunbun Bundjali; N. M. Surdia; Oei Ban Liang; Bambang Ariwahjoedi (Institut Teknologi Bandung, 2004)
The pH-potential, or the so called Pourbaix, diagram for the system Fe - H2O is normally been constructed by using thermodynamic data. In this work the diagram was constructed experimentally based on potentiodynamic measurements of carbon steel in acetic acid - acetate ion buffer solutions at a temperature range of 25-85 0C. Due to the limited pH trajectory of buffer acetate solutions the resulted diagrams were not as wide pH as those of thermodynamic Pourbaix diagrams, but they are more useful for analysing carbon steel corrosion in acetate environment systems at that temperature range. In Addition the effects of pH and temperature on the primary passive potential (Epp) and Fladge potential (EF) relationship could also be obtained.